2020
DOI: 10.1007/s00705-019-04488-3
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant infectious bronchitis virus from a chicken with a spike gene closely related to that of a turkey coronavirus

Abstract: Using viral metagenomics, the complete genome sequence of an infectious bronchitis virus (IBV) strain (named ahysx-1) from a fecal sample from a healthy chicken in Anhui province, China, was determined. The genome sequence of ahysx-1 was found to be very similar to that of IBV strain ck/CH/LLN/131040 (KX252787), except for the spike gene region, which is similar to that of a turkey coronavirus strain (EU022526), suggesting that ahysx-1 is a recombinant. Recombination analysis and phylogenetic analysis based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…Coronaviruses, as known as zoonotic pathogens, belong to the Coronaviridae family of the order Nidovirales. The Coronavirus genome consists of a single‐stranded positive‐sense RNA (+ssRNA) (∼30 kb) that is linked with a 3′poly-A tail (crown-shape peplomers with 80-160 nM in size) and a structure of 5′‐terminal cap [29] . Coronaviruses have the largest genomes (26.4e31.7 kb) among all known RNA viruses.…”
Section: Coronavirusesmentioning
confidence: 99%
“…Coronaviruses, as known as zoonotic pathogens, belong to the Coronaviridae family of the order Nidovirales. The Coronavirus genome consists of a single‐stranded positive‐sense RNA (+ssRNA) (∼30 kb) that is linked with a 3′poly-A tail (crown-shape peplomers with 80-160 nM in size) and a structure of 5′‐terminal cap [29] . Coronaviruses have the largest genomes (26.4e31.7 kb) among all known RNA viruses.…”
Section: Coronavirusesmentioning
confidence: 99%
“…In 2008, the genome of a CoV causing severe enteritis in turkeys was sequenced [ 268 ] and its origin was ascribed probably to a mutation of the IBV of chickens [ 269 ] that allowed the virus to acquire tropism for the intestinal tract. Additionally, a recombinant strain of IBV with TCoV has been recently identified [ 270 ].…”
Section: Coronavirus Diseases In Animalsmentioning
confidence: 99%
“…Trees based on different regions of the genome of RabPyV showed discordant results, suggesting that this novel rabbit polyomavirus had undergone genetic recombination. To determine whether RabPyV is a recombinant, the complete genome sequences of CPyV (DQ192570), GHPV (AY140984), PPyV (DQ192571), CommonPyV (NC_028119), and BankPyV (KR612372) were aligned with that of RabPyV using CLUSTAL X, and recombination analysis was performed using the Recombination Detection Program 4.0 (RDP 4.0), which includes seven different methods: RDP, GENECONV, BootScan, MaxChi, Chimaera, SiSCan and 3Seq [28]. The results of a manual bootscan analysis suggested that RabPyV resulted from a recombinant event occurring between the major parent NC_028119 and the minor parent DQ192570, with a high degree of confidence (P = 3.662 × 10 −6 ).…”
Section: A Novel Polyomavirus In Oral Samplesmentioning
confidence: 99%
“…The untranslated regions (UTRs) at the 5′ and 3′ ends usually contain structural elements and are related to replication and/or translation. The replicase gene, which occupies the 5′ two thirds of the CoV genome encodes the non-structural proteins, and the remaining one third encodes four major structural proteins, including the spike (S), membrane (M), envelope (E) and nucleocapsid (N) proteins [28,40]. CoVs are classified into four genera: Alphacoronavirus, Betacoronavirus, Gammacoronavirus, and Deltacoronavirus.…”
Section: Coronaviruses In the Fecal Samplesmentioning
confidence: 99%